The impact of taxation on investment and development in developing countries: a case of Zimbabwe - Mhizha, Takunda Samantha (Midlands State University, 2018)
The study critically analysed the impact of taxation on investment and development. Desk research was employed with data being sourced from books, publications and the internet. The study was aimed at examining the impact of taxation on investment in Zimbabwe; to determine whether the extent of cross sectional allocation of resources through tax revenue has impacted on the level of development in Zimbabwe and to establish measures that can be adopted for taxation to be an aid of economic growth. Various literatures was implored – both theoretical and empirical and evidence from the literature show that taxation has an impact on investment and development. Most of the literature pointed that the impact is on the increase across the globe due to the economic climate. This study found that taxation is an important factor which determines the investors’ choice of an investment destination. However, it is not a sufficient condition; there are a number of other conditions which include political stability, macroeconomic stability, and availability of skilled workforce, developed infrastructure and road network among others. The study also found that taxation has a positive condition on development. Revenue collected through taxation is allocated by government to fund projects for development. A number of these projects were identified and they include construction of schools, building dams, building clinics in rural areas among others. The study also recommended strategies which the government can adopt in order to strengthen the impact of taxation on investment and development. The strategies include reforming tax policy so as to reduce the tax burden on companies thereby increasing their income after taxation. The government was also recommended to allocate resources equitably.